APLIKASI EKSTRAK LIKOPEN DARI BUAH TOMAT APEL (Lycopersicum pyriforme) TERSALUT MALTODEKSTRIN PADA PENGOLAHAN MIE INSTAN FUNGSIONAL - Dini Noviyandari; Jaya Hardi; Mappiratu Mappiratu (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
A research about the application of lycopene extract of tomato fruit (Lycopersicum pyriforme) coated with maltodextrin in functional instant noodle processing has been done. The aim of the research was to determine the effect of lycopene coated with maltodextrin concentration on the shelf life of functional instant noodle. The goal was reached by using various of lycopene coated with maltodextrin concentration i.e. 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm and 2500 ppm. The functional instant noodle was kept at room temperature for 49 days and it was measured every 7 days. The result showed that the shelf life of functional instant noodle increased with the increase of lycopene coated with maltodextrin concentration. The longest shelf life (354.79 days) was found in 2500 ppm of maltodextrin concentration. Keywords: tomato, lycopene, instant noodle, shelf life